Turkey's nuclear energy policy in the context of environment: a case of Europeanization?. (8th August 2019) - Sever, S. Duygu
ABSTRACT: Combatting climate change and ensuring energy security require diversification of energy profiles through alternative resources, with nuclear energy being the most controversial one. Although the preferences among its members differ, the EU offers a specific legal and practical framework for nuclear energy. Turkey, on the other hand, emerges as a 'newcomer' in the nuclear energy field, revealing a need for policy learning for safe and secure nuclear energy generation. This research focuses on the Europeanization of Turkey's nuclear policy to trace whether a strategic or social learning takes place within the nuclear energy framework. The analysis also questions to what extent the EU and Turkey's framing of nuclear energy coincides or diverges with reference to the climate change.